Tranglutaminase 2 contributes to the asthmatic inflammation by modulating activation of alveolar macrophages - Hyun Seung Lee (Immunity, Inflammation and Disease, 2021)
Abstract Background Transglutaminase 2 (TG2), a multifunctional calcium‐dependent acyltransferase, is upregulated in asthmatic airways and reported to play a role in the pathogenesis of allergic asthma. However, the underlying mechanism is not fully understood. Objective To investigate the role of TG2 in alternative activation of alveolar macrophages by using murine asthma model. Methods TG2 expression was assessed in induced sputum of 21 asthma patients and 19 healthy controls, and lung tissue of ovalbumin (OVA)‐induced murine asthma model. To evaluate the role of TG2 in asthma, we developed an OVA asthma model in both TG2 null and wild‐type mice. The expression of M2 macrophage markers was measured by fluorescence‐activated cell sorting (FACS) after OVA sensitization and challenge. To evaluate the effect of TG2 inhibition in vitro, interleukin 4 (IL‐4) or IL‐13‐stimulated expression of M2 macrophage markers was measured in CRL‐2456 cells in the presence and absence of a TG2 inhibitor. Results The expression of both TG2 and M2 markers was increased in the sputum of asthmatics compared with that of healthy controls. The expression of TG2 was increased in macrophages of OVA mice. Airway hyperresponsiveness, and the number of inflammatory cells, including eosinophils, was significantly reduced in TG2 null mice compared with wild‐type mice. Enhanced expression of M2 markers in OVA mice was normalized by TG2 knockout. IL‐4 or IL‐13‐stimulated expression of M2 markers in alveolar macrophages was also attenuated by TG2 inhibitor treatment in vitro. Conclusion Our results suggest that TG2‐mediated modulation of alveolar macrophage polarization plays important roles in the pathogenesis of asthma.